2020
DOI: 10.22603/ssrr.2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Outcomes of Spinal Fusion for Osteoporotic Vertebral Fractures in the Lower Lumbar Spine with a Neurological Deficit

Abstract: are the Editorial Board members of Spine Surgery and Related Research and on the journal's Editorial Committee. They were not involved in the editorial evaluation or decision to accept this article for publication at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Neurological compromise following LVF is relatively rare. According to a recent multicenter cohort study, 6 ) number of the thoracolumbar junction fractures causing neurological deficits was five times that of lower lumbar fractures causing radiculopathy. Thoracolumbar junction fractures commonly cause anterior-wedge vertebral deformity, while LVF commonly develops a concave deformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurological compromise following LVF is relatively rare. According to a recent multicenter cohort study, 6 ) number of the thoracolumbar junction fractures causing neurological deficits was five times that of lower lumbar fractures causing radiculopathy. Thoracolumbar junction fractures commonly cause anterior-wedge vertebral deformity, while LVF commonly develops a concave deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiculopathy usually lacks severe neurological deficits, it is often resistant to conservative therapies and so severe that it negatively impacts patient's daily activities. 1 - 6 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, sarcopenia is implicated in causing spinal sagittal imbalance due to insufficient compensation [35]. An OVF often necessitates fusion surgery [36]. Meta-analysis revealed that implant failure is considerably higher in osteoporotic spines than with normal bone mineral density [37].…”
Section: Introductionmentioning
confidence: 99%
“…Low lumbar OVC is also frequently found in patients with lower bone mineral density (BMD) and a higher mechanical failure rate, compared with thoracolumbar junction collapse 3 . Complications after surgery for OVC occurred in 14.1% of cases in a multicenter cohort study, with age, liver disease, and Parkinson’s disease (PD) found to be independent risk factors for postoperative complications 4 .…”
Section: Introductionmentioning
confidence: 99%